2020
DOI: 10.1021/acsomega.0c04883
|View full text |Cite
|
Sign up to set email alerts
|

Valorization of Wheat Straw for the Paper Industry: Pre-extraction of Reducing Sugars and Its Effect on Pulping and Papermaking Properties

Abstract: Cleaner production of sugars and pulp from renewable feedstocks has captured significant scientific attention in the recent past because they can be used for various end applications. In the papermaking industry, a major fraction of hemicellulosic sugars is lost during the pulping. The present study aims at retrieving these hemicellulosic sugars through alkali-, hot-water-, and acid-mediated extraction prior to pulping, which otherwise would have been lost during pulping and washing of pulp. These retrieved su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 30 publications
1
18
1
1
Order By: Relevance
“…Our finding of the improved pulping yield of acid pre-treated material is of great importance, as the previous study suggested that, acid leaching did not affect the pulping yield rather it improved delignification rate [24]. Improved pulping yield for the acid pretreated wheat stubble was also reported earlier near to 10.6% at 16% of alkali charge, which is close conformity with our finding [28]. Related to our finding of lower AA demand of acid pretreated material during pulping was suggested and it could be due to a decline in the extractive content [13].…”
Section: Effects On Pulping Yield and Degree Of Polymerizationsupporting
confidence: 93%
See 2 more Smart Citations
“…Our finding of the improved pulping yield of acid pre-treated material is of great importance, as the previous study suggested that, acid leaching did not affect the pulping yield rather it improved delignification rate [24]. Improved pulping yield for the acid pretreated wheat stubble was also reported earlier near to 10.6% at 16% of alkali charge, which is close conformity with our finding [28]. Related to our finding of lower AA demand of acid pretreated material during pulping was suggested and it could be due to a decline in the extractive content [13].…”
Section: Effects On Pulping Yield and Degree Of Polymerizationsupporting
confidence: 93%
“…3. Even though the earlier report confirmed the enhanced lignin content of wheat straw up to 25.67% due to pretreated with 0.1N H 2 SO 4 at 125̊C for 120 minutes [28]. While in the case of extractive removal, acid pretreatment caused its removal to a greater extent at higher pH and high retention time, it means increased pH (1.5-2.5) and increased retention time (0.5-1.5 hr) resulted in higher removal of extractive from 24.8 to 50% and from 26.9 to 65.4 % respectively, while increased consistency resulted in decreased extractives removal as shown in Fig.…”
Section: B Effects On Chemical Constituentsmentioning
confidence: 83%
See 1 more Smart Citation
“…Соотношение вышеуказанных групп зависит от источника лигнина [7]. Сухая масса клеточной стенки на 20-35% состоит из лигнина, в зависимости от растения, мягкая древесинана 25-35%, а лиственная древесинана 20-25% [8].…”
unclassified
“…2 Compared with conventional energy, crop straw is a renewable resource that can be completely degraded by composting over a short period. Crop straw contains cellulose, hemicellulose and lignin that can be used for ethanol production, 5,6 feed production, 7,8 paper making, 9,10 agricultural fertilizers, 11,12 edible fungi cultivation, 13,14 etc. The efficient use of crop straw can save the consumption of traditional energy, such as crude oil and natural gas.…”
mentioning
confidence: 99%